THE SIGNIFICANCE AND NECESSITY OF DIGITALIZATION OF THE SERVICE FIELD - Mirzaev Kulmamat Djanzakovich (Web of Journals Publishing, 2024)
This article presents the author's views on the development of the service sector and digitalization issues. Also, proposals and recommendations for the digitalization of the service sector were developed.
Keywords: service, service, digital, digitalization, digital economy, digital service, blockchain, cloud technologies, diversification, modernization, innovation.